Revitalisasi Peran Politik Umat: Urgensi Integrasi Islam dan Politik dalam Realitas Bernegara - Harun, Hermanto (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
The role of Muslims in politics today was diminishing. Muslims as just being a spectator in the political dynamics associated with the maintenance of state power. Religion and politics seemed to be two entities were no longer allowed to put together, even when using the label of religion in politics was often accused of being a seller sacred teachings in order to achieve a position of power. In fact, religion and politics in Islam were the two entities that could not be separated, since the foundation of the unity of the state was religion and politics into a medium in keeping religion itself. This paper would explain the importance of understanding the plenary about the relation between religion and politics. Understanding of religion should depart from the text of scripture which was then convinced by logical reasoning religious purposes, further supported by the socio-political reality in the state. Finally, the poin from this study stated that the political role of community revitalization step was very urgent to do with how to install, or at least to update again the understanding of Muslims about Islam and political integration in the reality of the state. Thus, the nature of Islam as a religion could be found.